(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
Region of disease locations of puccinia and resistance varieties of wheat. Integration of plant protection of wheat to disease, the causative agents of which are fungi.